The Anthropogenic Pressure On Nature Environment Of Rivne Region - Войчун, Н. І.; Андрейчук, Ю. М.; Жданюк, Б. С. (Man and Environment. Issues of Neoecology)
Purpose. Analysis of anthropogenic impact on the environment Rivne region. Methods. Geoinformation method, system ArcGIS. Results. In the article was analyzed pollution sources of Rivne region nature environment. Also was studied industrial complex and prevailing branches of industry features. The detailed long-term analysis made for anthropogenic impact on region air. Characterized main pollutants of atmospheric air. Using geoinformational system ArcGIS constructed series of GIS models that showed ecological condition of studied region. Conclusions. The main air pollutants are road transport and small businesses.